The Effects Of The Early Loss Of 1. Molars On The Vertıcal Dımensıons Of Dentofacıal System - Deniz Sağdıç; Bülent Özdoğan; Osman Bengi; Hüseyin Ölmez (Galenos Yayinevi, 1995)
The purpose of this investigation is to evaluate the effects of the early loss of 1. molars on the vertical facial dimensions. Our investigation was carried on 32 individuals who lost only upper first molars, 32 individuals who lost only lower first molars, 24 individuals who lost both upper and lower first molars and 32 individuals with normal occlusion and normal face. When the lateral cephalograms of 120 individuals were examined and statistically evaluated it has been found that, vertical alveoler growth, inclination of mandibular plane, bazal angle and the height of ramus were decreased and the amount of overbite were increased as a result of early loss of 1. molars.